2012
DOI: 10.21000/jasmr12010325
|View full text |Cite
|
Sign up to set email alerts
|

Switchgrass Potential on Reclaimed Surface Mines for Biofuel Production in West Virginia

Abstract: The high cost and environmental risks associated with non-renewable energy sources has caused an increased development of renewable biofuels. Switchgrass (Panicum virgatum L.), a warm-season perennial grass, has been investigated extensively as a source of biofuel feedstock due to its high biomass production on marginal soils. Additionally, the plant's high tolerance to adverse growing conditions and its ability to provide habitat for wildlife makes it a widely used species for conservation cover. West Virgini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Weeds were found in appreciable quantities in the stands during the first and second years after planting, but they declined in 2012 as the switchgrass shaded and out-competed the weeds. Switchgrass stands do not develop fully until after the third growing season (Marra and Skousen, 2012). Therefore with less competition from weeds and greater stand density and growth, target yields are anticipated to be reached.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weeds were found in appreciable quantities in the stands during the first and second years after planting, but they declined in 2012 as the switchgrass shaded and out-competed the weeds. Switchgrass stands do not develop fully until after the third growing season (Marra and Skousen, 2012). Therefore with less competition from weeds and greater stand density and growth, target yields are anticipated to be reached.…”
Section: Resultsmentioning
confidence: 99%
“…Switchgrass has been used in reclamation studies on roadsides (Skousen and Venable, 2008), surface mines (Skeel and Gibson, 1996;Marra and Skousen, 2012;Dere et al, 2011), sand and gravel mines (Gaffney and Dickerson, 1987), lignite overburden (Skousen and Call, 1987), and Pb and Zn mines (Levy et al, 1999). In 2008, switchgrass trials were established for bioenergy production in West Virginia (Marra and Skousen, 2012). They found that switchgrass on reclaimed land with topsoil produced yields of nearly 7,000 kg ha -1 , but yields were three times lower (2,000 kg ha -1 ) on reclaimed lands with no topsoil.…”
Section: Switchgrassmentioning
confidence: 99%